Corticospinal Excitability Is Lower During Eccentric Than Concentric Cycling in Men - Clos, Pierre; Mater, Adrien; Legrand, Hippolyte; Poirier, Gabriel; Ballay, Yves; Martin, Alain; Lepers, Romuald (Frontiers in Physiology, 2022)
How corticospinal excitability changes during an eccentric locomotor exercise is unknown. In the present study, 13 volunteers performed 30-min strenuous concentric and eccentric cycling bouts at the same power output (60% peak power output). Transcranial magnetic and electrical femoral nerve stimulations were applied at exercise onset (3rd min) and end (25th min). Motor-evoked potentials (MEPs) amplitude was measured for the rectus femoris (RF) and vastus lateralis (VL) muscles with surface electromyography (EMG) and expressed as a percentage of maximal M-wave amplitude (MMAX). Silent period duration and EMG amplitude 100 ms prior to MEPs were calculated. There was no change in any neural parameter during the exercises (all P > 0.24). VL and RF MMAX were unaffected by exercise modality (all P > 0.38). VL MEP amplitude was greater (26 ± 11.4 vs. 15.2 ± 7.7% MMAX; P = 0.008) and RF MEP amplitude tended to be greater (24.4 ± 10.8 vs. 17.2 ± 9.8% MMAX; P = 0.051) during concentric than eccentric cycling. While VL EMG was higher during concentric than eccentric cycling (P = 0.03), RF EMG showed no significant difference (P = 0.07). Similar silent period durations were found (RF: 120 ± 30 ms; VL: 114 ± 27 ms; all P > 0.61), but the silent period/MEP ratio was higher during eccentric than concentric cycling for both muscles (all P < 0.02). In conclusion, corticospinal excitability to the knee extensors is lower and relative silent period longer during eccentric than concentric cycling, yet both remained unaltered with time.